Identitet Bošnjaka Bosanaca kao intersekcijske socijalne grupe / The Identity of Bosniak Bosniand as an Intersectional Social Group - Smailagić, Vedad (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
In this paper, the author examines the current use of the ethnonym Bošnjak (Bosniak) and Bosanac (Bosnian) from the moment after the reactivation of the ethnonym Bošnjak. The analysis deals with the connection between the meaning and use of these two ethnonyms, taking into account the cultural and historical circumstances of the parallel existence of the social reference groups Bosanac and Bošnjak and their collective identities as well as their symbolic and value systems. Following this goal, the work is based on a linguistic analysis, which necessarily takes into account semantic aspects determined by cultural-historical and sociological contexts. At the end of the discussion on the meaning and use of these two ethnonyms, a model is outlined that describes the mutual relationship between Bosniaks and Bosnians as ethnically defined and ethnically named, as well as linguistically, culturally and socially extremely close collective identities.